Sejarah Perkembangan Kebijakan Ekonomi Pada Masa Orde Baru dan Pengaruh Krisis Moneter terhadap Perekonomian Indonesia - Puspa Unsya Shaleha; Anita Selviana; Indra Muharman (Analisis Sejarah, 2024)
The history of economic policy development during the New Order era in Indonesia reflects the political and economic dynamics that shaped the nation's development trajectory. Initially, the New Order government adopted a centralized and authoritarian economic development model, emphasizing industrialization and modernization. While these programs spurred economic growth, they also led to social inequality and political tensions. The late 1990s currency crisis, particularly the 1997 Asian financial crisis, significantly destabilized Indonesia's economy. Economic policies of the New Order era, characterized by dependence on foreign debt and imprudent monetary practices, rendered Indonesia susceptible to global financial market fluctuations. The impact of the crisis was profound, manifesting in a sharp decline in economic growth, a currency crisis, and a banking crisis, which compelled the government to implement urgent economic reforms. These reforms included financial sector restructuring, economic deregulation, and enhanced transparency in public financial management. This study provides an in-depth analysis of the New Order's economic policies and the subsequent impact of the currency crisis on Indonesia's economy.